Living large benthic foraminifera (LBF) on macroalgae at Mandalika, Lombok, Indonesia - Sri Devi Ananda; Imam Bachtiar; Lalu Japa (Universitas Malikussaleh, 2026)
Intertidal large benthic foraminifera make a large contribution to the sustainability of reef accretion in intertidal zones and sediment supply on the beach of the Special Economic Zone (SEZ) of Mandalika in the southern part of Lombok Island. Studies on these unicellular animals are rare in Indonesian waters. The present study aimed to describe living foraminifera at the intertidal zone of the Serinting Beach and their association with macroalgae. Data on the living foraminifera attached to macroalgae were collected using the transect quadrate method, 45 quadrates (1 sqm size) along three transects (⁓400 m length). The results revealed that three species living attached to macroalgae are Schlumbergerella floresiana, Schlumbergerella neotetraedra, and Sphaerogypsina globulus. The most abundant foraminifera species found attached to macroalgae was S. floresiana. A total of 20 species of macroalgae were found to be colonized by foraminifera. Five out of seven macroalgae genera were heavily inhabited by foraminifera: Chondrus, Padina, Halimeda, Amphiroa, and Acanthophora. Among these five macroalgae genera, the abundance of foraminifera was not significantly different. There was a significant association between foraminifera species and macroalgae genera. All three Foraminifera species showed a high preference for Halimeda macroalgae. The study suggests that sustainable tourism management at the SEZ Mandalika should take the five macroalgae genera into account to maintain sediment supply and reef accretion and sustain life below water.